PENGARUH UMUR PANEN PUCUK DAN KONSENTRASI POC URINE KELINCI TERHADAP PERTUMBUHAN DAN PRODUKSI PUCUK KENIKIR (Cosmos caudatus) - Dian Mardiansyah; Siti Nurhidayah; Ismail Saleh (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Kenikir is an indigenous plant that has the potential to be cultivated, but there are still many people who do not know the potential of kenikir. This research aims to study the effect of shoots harvest on the results of kenikir and to find the best concentration of liquid organic fertilizer rabbit urine for the growth of kenikir. This research was conducted in January - April 2020 in the experimentation field of Perjuangan University of Tasikmalaya at an altitude of 359 m asl. The design used was a two factor Randomized Complete Block Design (RCBD). The first factor is the age of harvest, consisting of 3 levels ie 7 WAP (Weeks after planting), 8 WAP and 9 WAP. The second factor is urine concentration consisting of 4 levels ie 0 ml.L-1, 10 ml.L-1, 20 ml.L-1 and 30 ml.L-1. The results showed that 10 ml of L-1 U2 treatment produced higher kenikir plants and thicker diameters. U2P3 treatment gave the best response to plant height variables. All treatment combinations gave the same response to the number of leaves harvested and the weight of fresh shoots